Association of Chronic Toxoplasma gondii Infection with Pro-Inflamatory Cytokine Interleukin (IL)-12 Responses in Type-2 Diabetes Mellitus Patients of Bangladesh - Tamanna Ashraf; Pankaj Kumar Sarker; Md. Ismail Hosen; Atiqur Rahman; A. K. M. Mahbub Hasan; Taibur Rahman (Journal of Parasitology Research)
Toxoplasma gondii is an intracellular protozoan parasite that causes toxoplasmosis in around one-third of the world population, particularly in pregnant women and immunocompromised individuals. Diabetes mellitus (DM) is one of the most severe global health challenges in the 21st century, and especially, type-2 diabetes mellitus (T2DM) accounts for 90% of the diabetes cases diagnosed globally. In Bangladesh, the rate of T2DM is rising gradually with the improvement in living standards. The aim of this study is to find out the correlation between latent toxoplasmosis and T2DM, emphasizing the pro-inflammatory cytokine immunity. For this, 100 (N=100) patients with T2DM and 100 (N=100) healthy controls were enrolled to determine the seroprevalence of toxoplasmosis using enzyme-linked immunosorbent assay (ELISA). In addition, ELISA was also performed to determine the level of pro-inflammatory cytokine, interleukin (IL)-12, to understand its role in the development of toxoplasmosis. In our study, 39.39% of the T2DM patients were positive with anti-T. gondii Immunoglobulin G by ELISA, whereas the rate of seropositivity in healthy controls was 39.73%. We did not find significant association between T. gondii infection and T2DM, but our data confirmed a high prevalence of chronic toxoplasmosis in Bangladeshi population. From hematology tests, it was found that the T2DM patients had significantly lower levels of total white blood cells (P=0.0015), circulating eosinophils (P=0.0026), and neutrophils (P=0.0128) than the healthy controls. On the other hand, the levels of lymphocytes (P=0.0204) and monocytes (P=0.0067) were significantly higher in patients. Furthermore, T. gondii infected T2DM patients had significantly higher levels of IL-12 than the healthy controls (P=0.026), suggesting a link between parasitic infection and IL-12 secretion. Further studies are to be performed to find out the exact cause of high prevalence of chronic T. gondii infection in Bangladeshi population.